Does presenting perpetrator and innocent suspect faces from different facial angles influence the susceptibility of eyewitness memory? An investigation into the misinformation effect and eyewitness misidentification - Kara Deering; Melissa F. Colloff; Tia C. Bennett; Heather D. Flowe (Frontiers in Psychology, 2024)
IntroductionThis study investigated the effects of face angle congruency across stages of a misinformation paradigm on lineup discrimination accuracy.MethodsIn a between-subjects design, participants viewed a mock crime with the perpetrator’s face from the front or profile angle. They then read a news report featuring an innocent suspect’s image from the same or different angle as the perpetrator had been shown. A subsequent lineup manipulated perpetrator presence and viewing angle of the lineup members, who were all shown either from the front or in profile.ResultsNo significant difference emerged in identification errors based on angle congruency between stages. However, accuracy was higher when faces were shown from the front angle, both during the initial event and the lineup, compared to the profile angle.DiscussionThe results of this research underscore the importance of considering viewing angles in the construction of lineups.